2001
DOI: 10.1128/jcm.39.5.1731-1737.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Aspergillus fumigatus in Clinical Samples from Patients with Invasive Aspergillosis: Investigation Using Multiple Typing Methods

Abstract: The genotypes of 52 strains of Aspergillus fumigatus isolated from 12 patients with invasive aspergillosis were investigated using three typing methods (random amplified polymorphic DNA, sequence-specific DNA polymorphism, and microsatellite polymorphism) combined with multilocus enzyme electrophoresis. Isolates were from patients hospitalized in three different geographic areas (Lyon, France; Grenoble, France; and Milan, Italy). In each case, the genetic polymorphism of several colonies (two to five) within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 41 publications
7
34
2
1
Order By: Relevance
“…Our result is consistent with earlier studies of more limited scope, for example, no correlation was found between genotype and geography for European and North American individuals (Debeaupuis et al 1997), nor for isolates from French and Italian patients (Bertout et al 2001), nor for environmental and clinical isolates from Canada (Rosehart et al 2002). Neither has any correlation between genotype and geography been found in another, study using a different collection of A. fumigatus individuals and different genetic markers (Rydholm et al 2003).…”
Section: Biogeographysupporting
confidence: 83%
“…Our result is consistent with earlier studies of more limited scope, for example, no correlation was found between genotype and geography for European and North American individuals (Debeaupuis et al 1997), nor for isolates from French and Italian patients (Bertout et al 2001), nor for environmental and clinical isolates from Canada (Rosehart et al 2002). Neither has any correlation between genotype and geography been found in another, study using a different collection of A. fumigatus individuals and different genetic markers (Rydholm et al 2003).…”
Section: Biogeographysupporting
confidence: 83%
“…Several previous studies have demonstrated that patients with invasive aspergillosis might be infected by more than one strain (7,8,18). Colonization with multiple A. fumigatus genotypes in the CGD patient has also been shown in patients with cystic fibrosis (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic methods include several techniques, such as random amplified polymorphic DNA (RAPD) analysis (1,10,11), restriction fragment length polymorphism (RFLP) analysis (13), amplified fragment length polymorphism (AFLP) analysis (18), and microsatellite length polymorphism (2). The last technique is sometimes also called microsatellite polymorphism analysis (5) or polymorphic microsatellites marker analysis (8). However, a major problem with pattern-based techniques, such as RAPD, RFLP, and AFLP analyses, is the poor interlaboratory reproducibility.…”
mentioning
confidence: 99%